STORY GRAMMAR STRATEGY: AN APPROACH TO TEACH READING NARRATIVE TEXT - Nuriyatul Hamidah (IAIN MADURA, 2016)
Teaching English as Foreign Language emphasizes on teaching discourse in the classroom. This paper is presented focusing on conceptual paper in teaching reading. Specifically, this study focuses on written discourse discussing on the use of narrative text to teach students’ reading skill. In foreign language teaching, teaching reading is one of important goal that students want to achieve. This paper focuses on one of English text type that is narrative text. It covers the theoretical basis dealing with the method of teaching reading, the use of narrative text that applies the text discourse analysis and the use of story grammar strategy. Furthermore, it also covers the teaching procedure (pre-teaching, whilst-teaching, post-teaching), reflection, and conclusion. Finally, it presents the reflection and conclusion of this analysis. The result shows that students’ comprehension can be enhance through story grammar in the teaching of reading narrative text along with appropriate assessment for them.